2022
DOI: 10.3389/fimmu.2022.1001055
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Epstein–Barr virus infection in patients with inflammatory bowel disease

Abstract: A high prevalence of Epstein–Barr virus (EBV) infection in patients with inflammatory bowel disease (IBD) has been reported in many case reports and studies; thus, the association between EBV and IBD has gained increasing attention. Patients with IBD are at an increased risk of opportunistic EBV infection owing to the common use of immunomodulators. EBV infection in IBD patients can cause various complications, including superimposed viral colitis, which is associated with chronicity, exacerbation, and poor pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“…As another member of the herpesvirus family, Epstein–Barr virus (EBV) has infected most of the world’s population (90%), in a form of latent lifelong infection, as an asymptomatic disease in childhood and as infectious mononucleosis (IM) in adulthood, a self-limiting disease (Jefremow and Neurath 2020 ; Zhang et al 2022 ). In a systematic review and meta-analysis, using 11 metagenomic studies, the EBV plus CMV was determined as a significant cause of IBD (Marongiu et al 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As another member of the herpesvirus family, Epstein–Barr virus (EBV) has infected most of the world’s population (90%), in a form of latent lifelong infection, as an asymptomatic disease in childhood and as infectious mononucleosis (IM) in adulthood, a self-limiting disease (Jefremow and Neurath 2020 ; Zhang et al 2022 ). In a systematic review and meta-analysis, using 11 metagenomic studies, the EBV plus CMV was determined as a significant cause of IBD (Marongiu et al 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…T cells, B cells and NK cells infections also occur, impairing cellular immunity. Additionally, the spread of infection into enterocytes causes epithelial or mucosal tissue damage (Zhang et al 2022 ). The misdiagnosis may occur due to the similarity of IBD and EBV-associated lymphoproliferative disorders (LPDs) (Patton et al 2018 ; Zhou et al 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Patients treated with anti-TNF have also been reported to develop shingles (symptomatic VZV reactivation), requiring treatment, and have been found to have EBV and CMV by PCR in the stool ( Kim and Solomon, 2010 ; Santella et al, 2022 ). In fact, other T-cell mediated autoimmune diseases, such as inflammatory bowel disease has been associated with reactivation of herpes viruses, as EBV has been found in the mucosal lining of the gut in some of these patients ( Zhang et al, 2022 ; Wang et al, 2022 ). Dysregulated immune responses to EBV have also been strongly linked to the immunopathogenesis of multiple sclerosis, as well as finding evidence of EBV in the brain ( Pender et al, 2017 , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Circulating miRNAs are widely distributed throughout the body, interacting with tissues and organs [ 40 ]. Bioinformatics studies have demonstrated that the target gene hsa-miR-320d is involved in the pathogenesis of inflammatory bowel disease [ 41 ], with elevated concentrations observed in the blood under inflammation-prone conditions [ 42 ]. Furthermore, this miRNA may be specific to systemic inflammatory disorders, including knee osteoarthritis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%